Beta-alanine supplementation provides added benefits to the effect of sprint-interval training on cycling performance - Bellinger, P.; Minahan, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Beta-alanine supplementation and sprint-interval training (SIT) have been independently shown to have positive effects on cycling time trial (TT) performance (Rønnestad et al., 2014; Bellinger et al., 2015). SIT following beta-alanine supplementation may lead to added benefits compared to SIT alone by allowing athletes to train at a higher intensity. The present study investigated the effects of betaalanine supplementation only, and in combination with SIT, on training capacity, and energy provision and performance during exhaustive supramaximal cycling and a 4-km TT. Methods: Trained cyclists (VO2max=4.5±0.6 L/min) performed a supramaximal cycling test to exhaustion (equivalent to 120% VO2max), a 4-km TT and 4 x 1-km sprints at 3 time points: before and after 4 wk of supplementation loding (6.4 g/day) with beta-alanine (BA=7) or a placebo (PL=7), and after 5-wk of supervised SIT (repeated 1-km maximal efforts) performed 2/wk whilst maintaining supplementation (1.2 g/day). Data was compared using a two-way ANOVA and contemporary magnitude-based inferences (Hopkins et al., 2009). Results: Beta-alanine supplementation alone increased anaerobic capacity (4.0±3.0%; P=0.03), supramaximal cycling TTE (8.9±8.4%; P=0.03), 4-km TT (1.7±1.7%; P=0.05) and sprint 3 and 4 of the 4 x 1-km sprints (2.1±2.0% and 1.9±1.2%; P<0.05, respectively) with no change in PL. Power output during the 1-km cycling sprints increased from the first to the last training session to a greater extent in BA compared to PL (BA: 12.9±6.4%; PL: 6.6±4.2; P=0.04). Following SIT, there were greater improvements in supramaximal cycling TTE (BA: 14.9±7.6%; PL: 9.0±6.9; P=0.04) and further worthwhile enhancements in 4-km TT performance (BA: 4.0±1.5%; PL: 2.9±1.5; P=0.28) in BA compared to PL, but this did not reach statistical significance. Anaerobic capacity (5.5±4.2%; P=0.04) and VO2 after 60-s of supramaximal cycling (2.9±1.9%; P=0.05) was higher in BA following training, but remained unchanged in PL, whilst VO2peak increased similarly in each group (BA: 3.1±2.9%; PL: 3.5±2.8; P=0.48). Discussion: These findings indicate that beta-alanine supplementation allowed for better maintenance of cycling performance during repeated bouts of cycling sprint intervals, thereby allowing cyclists to consistently train at a higher intensity during a SIT program. Furthermore, this provided additional worthwhile benefits to exhaustive supramaximal cycling and 4-km TT performance compared to training alone. The additive benefits to performance following beta-alanine supplementation, in combination with SIT, appear to be related to superior aerobic and anaerobic adaptations.